1924
DOI: 10.1002/cber.19240570815
|View full text |Cite
|
Sign up to set email alerts
|

Beiträge zur Kenntnis der Indigo‐gruppe, IV.: Über einen neuen aus Indigo und Phenylessigester entstehenden Küpenfarbstoff

Abstract: M'ic der eine von uns2) gefunden hat, 1iiDt sich I n d i g o mit verschiedci:en 1: : c, Ic r II kondensieren, welche eine r e a k t i o n s f $11 i g e M e t 11 y leng r U p p c enthslten, und zwar unter Bildung neuer K ii p e n f a r b s t o f f e , welchc erheblich rotstichiger farben, als der Indip selbst. Die IConstitution des einen, auf diese Weise aus Indigo und M a l o n s a u r e -d i a t h y l -::s t e r eritstehenden Farbstoffs, der kurz als ))Indigo -malonestercc bezeicliriet wurde, konnte von dem e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1924
1924
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The condensation of indigo 175.1 with ethyl phenylacetate or phenylacetyl chloride furnishes the fused 1,5-naphthyridine 175.2 known as Cibalackrot (Ciba Lake Red B), which is an industrial dye with photophysical properties very different from those of indigo (Scheme ). The compound was described in the 1910s by Engi (see ref ) and subsequently by Posner and Kemper . The condensation was shown to work with other indigo derivatives, for example, with β-naphthindigo, yielding 175.3 , as well as with other arylacetyl derivatives.…”
Section: Nonbenzenoid Fusionmentioning
confidence: 99%
See 2 more Smart Citations
“…The condensation of indigo 175.1 with ethyl phenylacetate or phenylacetyl chloride furnishes the fused 1,5-naphthyridine 175.2 known as Cibalackrot (Ciba Lake Red B), which is an industrial dye with photophysical properties very different from those of indigo (Scheme ). The compound was described in the 1910s by Engi (see ref ) and subsequently by Posner and Kemper . The condensation was shown to work with other indigo derivatives, for example, with β-naphthindigo, yielding 175.3 , as well as with other arylacetyl derivatives.…”
Section: Nonbenzenoid Fusionmentioning
confidence: 99%
“… a Reagents and conditions: (a) reflux; (b) MeOCH 2 Cl, 100 °C, 20 h; (c) PI 3 , DCM, 12 h; (d) BI 3 , DCM, 12 h; (e) mesitylene, 100 °C, 3.5 h. …”
Section: Nonbenzenoid Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…73095 [6417-51-2]). Its synthesis was described by Engi in 1911 (from the Gesellschaft fuer Chemische Industrie in Basel) and Posner and its basic fluorescent properties studied by Birckner, Hauke and Paetzold. , More recently, laser flash photolysis and fluorescence results have been presented . Besides these works, only two Japanese patents on it as an electrophotographic photoreceptor , and an optoelectronic device 31 with high-energy conversion efficiency are found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…One limitation to our previous approach was the use of indigo exclusively as a nucleophile, initiating cascade reactions following treatment with a base. Recent studies have shown indigo to be a competent carbonyl-based electrophile, exemplified by reactions with arylamines in the presence of strong Lewis acids, , and tandem acylation–condensation reactions with substituted acyl chlorides, while older reports describe reactions of indigo’s carbonyl groups with amines, hydrazine, and hydroxylamine, among others. Given both the reported unreliability of some older methods, , and that in near-to-all cases, these methods predate all contemporary spectroscopic techniques, re-examination of indigo’s electrophilic potential is of considerable importance. Although the reaction of simple Grignard reagents was first noted in 1909, it was confined to the nucleophilic addition only, with no subsequent elaboration, and just simple alkyl Grignard reagents used, with characterization limited to chemical analysis.…”
mentioning
confidence: 99%